From the shadows. - Bhavan Jaipragas. (2013)
From the Shadows is an illustrated feature-writing project about the lives of Malaysia’s marginalised ethnic Indian community, and their likely impact on the country’s 13th general election in May 2013. The project was published a few days ahead of the landmark polls, and was picked up by news media outlets in Singapore and Malaysia.